Design of hydroxyapatite bioceramics with micro-/nano-topographies to regulate the osteogenic activities of bone morphogenetic protein-2 and bone marrow stromal cells. Issue 13 (20th March 2020) - Li, Xiangfeng; Liu, Minjun; Chen, Fuying; Wang, Yuyi; Wang, Menglu; Chen, Xuening; Xiao, Yumei; Zhang, Xingdong
Abstract : Biomimicking the nanostructure of natural bone apatite to enhance the bioactivity of hydroxyapatite (HA) biomaterials is an eternal topic in the bone regeneration field. Abstract : Biomimicking the nanostructure of natural bone apatite to enhance the bioactivity of hydroxyapatite (HA) biomaterials is an eternal topic in the bone regeneration field. In the present study, we designed four kinds of HA bioceramics with micro- to nanosized grains and investigated the effects of bioceramic topographies on the structures of bone morphogenetic protein-2 (BMP-2) and the effects on the responses of bone marrow stromal cells (BMSCs). Compared to the samples with submicron-scale crystalline particles, HA bioceramics with grain sizes of 104.6 ± 27.8 nm exhibited increased roughness, improved hydrophilicity and enhanced mechanical properties. The synergistic effects of these surface characteristics could well maintain the conformation of BMP-2, facilitate cell adhesion and spreading, and activate the osteogenic differentiation of BMSCs. Furthermore, SBF immersion and in vivo canine intramuscular implantation confirmed that the HA bioceramics with nanotopography also processed excellent bone-like apatite forming ability and outstanding osteoinductivity. In summary, these findings suggest that the nanotopography of HA bioceramics is a critical factor to enhance their bioactivity and osteoinductivity.